INVESTASI PERSPEKTIF AL-QUR’AN (STUDI MENGGUNAKAN METODE MAUDHU’I) - Nurlina Nurlina; Achmad Abubakar; Rusydi Khalid (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
No one can know what will happen in the future, so we must make preparations to meet the needs of life in the future. Efforts that can be made to meet the needs of life for sustainability and to maintain life is to invest. Investment is an effort to develop assets owned as allowed in Islamic teachings. The purpose of this study is to determine the perception of investment in the perspective of the Qur'an. In this study using qualitative methods through library research. The study of interpretation uses the maudhu'i approach. According to the research that has been done, it can be stated that the investment listed in the Qur'an and Hadith is a muamalah activity that is allowed as long as there is no violation in accordance with the rules of Islamic law. The findings show that there are several verses of the Qur'an relating to investment. The existence of investment activity means delaying consuming or using assets that are currently owned by developing and managing these assets in preparation for meeting future needs. As stated in the holy verse of the Qur'an Surah Yusuf/12:47-49, that the wealth we have should not be spent but the wealth must be managed again in order to prepare for life in the future. The existence of investment activity means delaying consuming or using assets that are currently owned by developing and managing these assets in preparation for meeting future needs. As stated in the holy verse of the Qur'an Surah Yusuf/12:47-49, that the wealth we have should not be spent but the wealth must be managed again in order to prepare for life in the future. The existence of investment activity means delaying consuming or using assets that are currently owned by developing and managing these assets in preparation for meeting future needs. As stated in the holy verse of the Qur'an Surah Yusuf/12:47-49, that the wealth we have should not be spent, but the wealth must be managed again in order to prepare for life in the future.